1991
DOI: 10.1007/bf00035130
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-beet seed steep treatments to improve germination under cold, wet conditions

Abstract: Modifying the present commercial sugar-beet steep treatment (12 h in 0 .2% thiram suspension, 25 °C) to include an initial 2 h steep in 0 .3 M hydrochloric acid, decreased fruit weight and cortex density and improved the performance of the inherently slower part of the population under cold, wet conditions . Adding gibberellins (GA4,7 ) or an N-substituted phthalimide (AC 94377) to the thiram steep was also beneficial whereas kinetin of N6-benzyladenine gave no improvement . Germination was even more rapid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…As found in the earlier study [5], it was the growth of the slowest part of the seedling population which was affected most by the treatments . The number of day degrees (above 3 °C) needed to achieve 0 .9 Hmax is shown in Fig .…”
Section: 1 Experimentssupporting
confidence: 56%
See 2 more Smart Citations
“…As found in the earlier study [5], it was the growth of the slowest part of the seedling population which was affected most by the treatments . The number of day degrees (above 3 °C) needed to achieve 0 .9 Hmax is shown in Fig .…”
Section: 1 Experimentssupporting
confidence: 56%
“…Recently, we confirmed that steeping sugar-beet seed in hydrochloric acid improved germination under cold, wet conditions [1,2,5] . The improvement in early growth was large enough to warrant further investigation .…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Pre-sowing seed treatments are use to leachout germination inhibitors, soften seed coats and advance physiological processes. Various methods such as soaking the seeds in water (Jun and Ling, 2004), osmotic solutions with known matric potentials (Kaffka et al, 1997), chilling and stratification (Schutz and Rave, 1999;Jun and Ling, 2004), temperature (Demel, 1996(Demel, , 1998Demel and Mulualem, 1996), physical scarification (abrasion, removal of seed coat layers), chemical scarification (with HCl, H 2 SO 4 and HNO 3 ), growth regulators and sound stimulation pretreatment significantly affect seed germination (Duan et al, 2004;khazaei, 2001;Bockarie and Duryea, 1993;Durrant and Mash, 1991) and have been recommended for improve seed germination in dormant seeds. Presowing seed treatments have been used in a number of crops to break dormancy or leachout chemical inhibitors from seed coat to get earlier and more uniform emergence.…”
Section: Introductionmentioning
confidence: 99%
“…Peto (1964) found out that sugar beet seed germination can be improved with dilute hydrochloric or sulforic acid treatment. Durrant and Mash (1991) reported that sugar beet seed treatment with 0.3 M hydrochloric acid improved seed germination. Akeson et al ( , 1981 showed that sugar beet seed treatment with dilute hydrochloric acid improved germination and emergence in laboratory and field experiment.…”
Section: Introductionmentioning
confidence: 99%